The complete works of the late Rev. Philip Skelton, rector of Fintona to which is prefixed Burdy's Life of the author - Skelton, Philip 1707-1787; Burdy, Samuel; Lynam, Robert; Princeton Theological Seminary; San Marino Community Church (London R. Baynes, 1824)
v. 1. Life of the Rev. Philip Skelton with some curious anecdotes; by Samuel Burdy. Controversial discourses.--v. 2. Discourses controversial and practical.--v. 3. Discourses, controversial and practical; A form of prayer for the use of families; Reflections on predestination; and a Summary of religion.--v. 4. Ophiomaches: or, Deism revealed.--v. 5. Several essays; and Juvenilia: consisting of Truth in a mask, etc.
Keywords: Skelton, Philip -- 1707-1787; Church History